Metodologija za ugotavljanje upravičenosti izvedbe krožnega križišča - Tollazzi, Tomaž (Urbani izziv, 2005)
In slightly less than twenty years roundabouts have become very popular in Slovenia. Lately, we can add, their acceptance is almost euphoric. Presently we have one roundabout on every 68 km of national roads, while their increasing quantity can be expected. In view of the fact that lately there have also been many unacceptable independent demands for their construction, in places where they would be unsuitable, the need for calming such desire is necessary. The article deals with the methodology for establishing acceptability for construction of roundabouts in urban environments and in their real physical circumstances.
Keywords: cestni promet; krožna križišča; Slovenia; Slovenija